Pragmatic Analysis of Social Meaning of Indonesian Language Towards Arabic Language Translation - Rizqiyah, Ulir; Anam, Syamsul; Maulana, Asep (Journal of Basic Education Research, 2025)
Purpose of the study: This research aims to analyzing the pragmatics of the social meaning of Indonesian which is then translated into Arabic Methodology: This study uses a qualitative method with a comparative study type of research, with a pragmatic analysis approach, the data source of this study is coption and speech acts of adolescents. The data collection technique of this researcher is the listening and recording technique. Main Findings: The speech acts of teenagers who follow the language of social media result in the person they are communicating with not being able to receive the information that the speaker wants to convey, this is what can result in different pragmatic social meanings. Novelty/Originality of this study: There are pragmatic differences in social meaning related to expressions of anger, disappointment, sadness and admiration in Indonesian which are then translated into Arabic. These expressions and speech acts differ in terms of the pragmatics of social meaning